Masterplan for the western expansion of Cuiabá: feasibility study based on climate-sensitive planning - Ana Carolina de Oliveira Lima; Takimoto, Emili Sayuri; Paiva, Fabio Friol Guedes de; Souza, Natallia Sanches e; Paula, Diana Carolina Jesus de (Scientific Journal ANAP, 2025)
Objective – The present study aims to propose guidelines for the elaboration of a Masterplan for the western region of Cuiabá-MT, incorporating the climate-sensitive urban planning approach, focusing on mitigating the effects of urban heat islands and promoting thermal comfort in contexts of continental tropical climate.Methodology – The Local Climate Zone (LCZ) classification methodology proposed by Stewart and Oke was adopted, based on urban morphology and land cover. The application of LCZs assesses urban occupation and guides Masterplan design decisions in accordance with legal and environmental guidelines.Originality/Relevance – The originality lies in the integration between the physical-spatial planning (Masterplan) and the microclimatic parameters of the LCZs, in a region of accelerated urban expansion and vulnerable to urban warming.Results – Industrial areas (LCZ2) and infrastructure areas (LCZ5) were strategically positioned along highways to optimize logistics, while green corridors (LCZA and B) were inserted as environmental mitigators, promoting thermal comfort and air quality. Community facilities (LCZ6) were planned alongside residential zones (LCZ4) and other urban areas (LCZs 3, 5 and 6), aiming to meet social demands and contain disorderly expansion, aligning land use with local reality and needs.Theoretical/Methodological Contributions – The study shows the Masterplan as a structuring instrument for urban climate planning, by integrating microclimatic variables into land use decisions, offering a methodological basis that can be replicated in tropical cities.Social and Environmental Contributions – The proposals promote equity in access to services, mitigate territorial inequalities, promote climate resilience and value environmental preservation, with emphasis on the creation of ecological corridors and the reduction of impacts of road infrastructures.
Keywords: Climate-sensitive planning; Urban resilience; Mato Grosso